Human factors and ergonomics: bridging psychology and technology in telemedicine applications. (1st September 2004) - Nichols, Timothy A.; Stronge, Aideen J.; Fisk, Arthur D.; Rogers, Wendy A.; Rasche, Jeanette; Sessions, G.
The field of human factors strives to optimise the performance, efficiency, and safety of human-machine systems by obtaining a clear understanding of the cognitive, perceptual and motor capabilities and limitations of users and their environment (both the physical environment and organisational climate). Thus, it is a science expressly devoted to many critical components of telemedicine systems. For example, telemedicine system users interact with potentially unfamiliar technology (e.g. digital cameras), individuals (e.g. doctors and patients), and information (e.g. technical instructions for a referring physician). In addition to these issues that users face on a regular basis, organisational issues exist, such as the management and overseeing of the system and the designation of various user roles within the system. Human factors researchers and practitioners employ multiple methods to evaluate psychological, macroergonomic, and usability issues that face users, as well as to provide design recommendations to improve system efficiency. These methods include task analysis, qualitative research methods (e.g. interviews and surveys), usability analysis, and quantitative research methods (e.g. questionnaires and experimental research). If telemedicine systems are to be successful and widely adopted, human factors evaluations and interventions must play a critical role in their development and continued improvement.